2019
DOI: 10.1016/j.foodchem.2019.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, oxygen and light on the degradation of β-carotene, lutein and α-tocopherol in spray-dried spinach juice powder during storage

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Effect of temperature, oxygen and light on the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 40 publications
1
36
1
Order By: Relevance
“…Spinach is rich in β‐carotene and lutein and α‐tocopherol. It is a good source of vitamin A, B complex, C, and K, calcium, magnesium, potassium, iron, and phosphorus, fiber, protein, oxalic acid, chlorophyll, and PC which contribute to its antioxidant capacity (Bhattacharjee et al., 1998; Çalışkan Koç & Nur Dirim, 2017; Citak & Sonmez, 2009; Lomnitski et al., 2003; Syamila et al., 2019).…”
Section: Spinach Juicementioning
confidence: 99%
See 1 more Smart Citation
“…Spinach is rich in β‐carotene and lutein and α‐tocopherol. It is a good source of vitamin A, B complex, C, and K, calcium, magnesium, potassium, iron, and phosphorus, fiber, protein, oxalic acid, chlorophyll, and PC which contribute to its antioxidant capacity (Bhattacharjee et al., 1998; Çalışkan Koç & Nur Dirim, 2017; Citak & Sonmez, 2009; Lomnitski et al., 2003; Syamila et al., 2019).…”
Section: Spinach Juicementioning
confidence: 99%
“…Effect of temperature (4, 20, and 40°C), oxygen and light on degradation of β‐carotene, lutein, and α‐tocopherol in spray‐dried SJ powder during storage were studied(Syamila et al., 2019). Excluding low fluorescent light intensity, and air, by vacuum packaging at 20°C did not improve nutrient retention loss over time.…”
Section: Spinach Juicementioning
confidence: 99%
“…Few studies have reported on the evaluation of the degradation kinetics of FAC and, especially, in powdered foods during storage, ignoring the exact mechanism that causes the degradation, which is why the problem is generally solved by adding a higher concentration before processing, so that the recommended level is present at the end of its commercial life. Among the works found, these generally evaluate the effect of storage conditions, like type of packaging (with O2, without O2, vacuum, with N2), TA, tS, RH, presence of light and generally predict the shelf life of the product stored: Chávez-Servín et al, [4], in powdered infant formula; Pua et al, [5], with powdered jackfruit (Artocarpus heterophyllus); Frias et al, [6], with enteral formulas; Jiménez-Aguilar et al, [7], with blueberry powder; Moraga et al, [8], with grapefruit powder; Kha et al, [9], with gac oil powder; Tan et al, [10], with bitter melon powder; Islam-Shishir et al, [11], with guava powder; Muzaffar and Kumar [12], with powdered tamarind pulp; Udomkun et al, [1], in dry papaya chunks; Araujo-Díaz et al, [13], with powdered blueberry juice; Zorić et al, [14], with cherry powder; Mahmoodani et al, [15], with powdered whole milk; de Moura et al, [3], with Hibiscus sabdariffa L; Syamila et al, [16], with powdered spinach juice.…”
Section: Postharvest Losses Do Not Only Include Physical Losses Inmentioning
confidence: 99%
“…βC‐fortified foods have been used to prevent vitamin A deficiency in preschool children and pregnant women; unfortunately, βC is fat‐soluble and weakly dispersed in most foods (Turner et al, 2013; Xiao et al., 2017). β‐Carotene efficiently quenches oxygen and free radical formation, thereby acting as an anti‐oxidant, anti‐inflammatory and anti‐cancer agent, and reducing the risk of chronic diseases (Dimakou & Oreopoulou, 2012; Syamila et al, 2019). This carotenoid is present in vegetables such as carrots, pumpkins, and sweet potatoes, which take its orange color, and also, together with anthocyanins, in vegetables such as purple carrots and tomatoes (Limón et al., 2015; Meng et al, 2019; Phan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%